Relationship between Zink and Anaemica in Chronic Haemodialysis Patients - Akhtar, Nasima; Ahsan, Raghib; Wakil, Md Abdul; Mostafa, CGM; Chowdhury, Sakhi; Hai, MA (TAJ: Journal of Teachers Association, 2009)
End stage renal disease (ESRD) patients receiving haemodialysis (HD) are frequently associated with anaemia. Zinc, being an important nutrient for haemoglobin synthesis, was studied for it's effect, if any, on renal disease associated anaemia among patients in the HD unit of BSMMU (formerly IPGMR), Dhaka. Surprisingly, a tow plasma zinc level and a high corpuscular (RBC) zinc level was observed. All of our subjects were found anaemic. A significant correlation was observed between plasma zinc level on one hand and haemoglobin level as well as RBC counts on the other hand. There are several suggestions for this low plasma and high corpuscular zinc level. However, this altered zinc level in plasma and red blood corpuscles might interfere with haemoglobin synthesis and might be one of the factors for renal disease associated anaemia. doi: 10.3329/taj.v16i1.3895 TAJ June 2003; Vol.16(1): 12-14